Analyzing Customer Satisfaction’s Effect as Intervening Variable of Service Quality Influencing Customer Loyalty: Indonesian Perspective - Novyandri Taufik Bahtera; Vina Firkiyatul Munawaroh (TIJAB (The International Journal of Applied Business), 2022)
Service quality is defined as a performance offered by a company to customers providing customer satisfaction and, in turn, can earn their loyalty. This study aims to analyse service quality effect on customer satisfaction, customer satisfaction on customer loyalty, and customer satisfaction as mediating service quality on customer loyalty. The method used inferential quantitative research. The data were collected by distributed online questionnaires on 43 customers of Islamic bank in East Java, Indonesia as the respondents. The data were processed by using the SmartPLS 3.0. The study’s result show a positive effect for service quality on customer satisfaction, a positive effect for customer satisfaction on customer loyalty, and a positive effect on customer satisfaction as mediating variable on service quality with customer loyalty. A company can get customer satisfaction if it provides excellent service quality and ultimately gets customer loyalty.